2009
DOI: 10.3844/ajebasp.2009.41.46
|View full text |Cite
|
Sign up to set email alerts
|

Managers Empowering Employees

Abstract: Problem statement: This article looked at the behavior of organizations as an important factor for empowering employees. This allowed for a greater level of partnering between managers and employees. The more that top management wants an internal commitment from its employees, the more it must involve employees in defining work objectives, specifying how to achieve them and setting stretch targets. Develop and improved and practical empowerment model that applies systems theory and socialization theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Managers' supportive behavior could increase staffs awareness of selfdetermination and their job proactiveness (Olham and Cummings, 1996). When organizations have managers empower their employees they are more productive (Carter, 2009). Thus leader's support plays an active role in employee and team performance.…”
Section: Leader's Support and Organisational Performancementioning
confidence: 99%
“…Managers' supportive behavior could increase staffs awareness of selfdetermination and their job proactiveness (Olham and Cummings, 1996). When organizations have managers empower their employees they are more productive (Carter, 2009). Thus leader's support plays an active role in employee and team performance.…”
Section: Leader's Support and Organisational Performancementioning
confidence: 99%
“…Several studies have shown that employees' perception of being considered important and being empowered will increase their level of emotional attachment to the organization (Allen & Meyer, 1990;Liden et al, 2000;Janssen, 2004;Chan, 2004). Sharing information and involving employees in decision making processes such as defining work objectives, specifying how to achieve them and setting stretch targets are necessary means of empowering employees (Carter, 2009). When employees are able to see the same information top managers see, their trust and loyalty develop -and both are vital to long term success.…”
Section: Introductionmentioning
confidence: 99%
“…Employees should be empowered to make an immediate decision to improve quality of the service for the customers (Wilkinson, 1998;Carter, 2009;Samad, 2007). Empowerment is one of the most important variables for the front-line employees.…”
Section: Front Line Employee Empowermentmentioning
confidence: 99%